Neural function in DCC mutation carriers with and without mirror movements. Issue 3 (4th February 2019) - Vosberg, Daniel E.; Beaulé, Vincent; Torres‐Berrío, Angélica; Cooke, Danielle; Chalupa, Amanda; Jaworska, Natalia; Cox, Sylvia M. L.; Larcher, Kevin; Zhang, Yu; Allard, Dominique; Durand, France; Dagher, Alain; et al.
Abstract : Objective: Recently identified mutations of the axon guidance molecule receptor gene, DCC, present an opportunity to investigate, in living human brain, mechanisms affecting neural connectivity and the basis of mirror movements, involuntary contralateral responses that mirror voluntary unilateral actions. We hypothesized that haploinsufficient DCC +/− mutation carriers with mirror movements would exhibit decreased DCC mRNA expression, a functional ipsilateral corticospinal tract, greater "mirroring" motor representations, and reduced interhemispheric inhibition. DCC +/− mutation carriers without mirror movements might exhibit some of these features. Methods: The participants (n = 52) included 13 DCC +/− mutation carriers with mirror movements, 7 DCC +/− mutation carriers without mirror movements, 13 relatives without the mutation or mirror movements, and 19 unrelated healthy volunteers. The multimodal approach comprised quantitative real time polymerase chain reaction, transcranial magnetic stimulation (TMS), functional magnetic resonance imaging (fMRI) under resting and task conditions, and measures of white matter integrity. Results: Mirror movements were associated with reduced DCC mRNA expression, increased ipsilateral TMS‐induced motor evoked potentials, increased fMRI responses in the mirroring M1 and cerebellum, and markedly reduced interhemispheric inhibition. The DCC +/− mutation, irrespective of mirror movements, was associated with reduced functional connectivity and white matter integrity. Interpretation: Diverse connectivity abnormalities were identified in mutation carriers with and without mirror movements, but corticospinal effects and decreased peripheral DCC mRNA appeared driven by the mirror movement phenotype. ANN NEUROL 2019;85:433–442.